Determinasi Nilai SPF Gel Ekstrak Etanol Kayu Manis (Cinnamomum burmannii) Secara In Vitro dan Uji Iritasi secara In Vivo. - Jainer Pasca Siampa; Weny Indayany Wiyono; Julianri Sari Lebang (Jurnal MIPA, 2023)
Cinnamon extract gel has been shown to have strong antioxidant effectiveness making it a candidate for sunscreen. One of the parameters to determine the ability of sunscreen to protect the skin is through the calculation of the SPF value. This study aimed to determine the SPF value in vitro using the UV-Vis spectrophotometry method. The results showed that the cinnamon extract gel had an average SPF value of 5.301 Â±0.080. Based on these results, it was concluded that the Gel had activity as sunscreen with moderate protection category.